Marphological structure of soybean vegetation and seeds - Jamoliddinov Javohir Elmurod o’g’li; Xurramova Gulsevar Xudoynazar qizi; Normurodova Sabina To’lqin qizi; Raimjonova Gulsora Soyibjon qizi (Genius Journals, 2023)
This article provides information on the morphology of the soybean plant and its seeds which are cultivated as oil crops belonging to the legume family
Keywords: Soybean plant; oil crop